The MIC and MBC of calcium hydroxide medicament against bacteria that cause chronic periapical abscess in the vulnerable initial 7-days of endodontic treatment - Putri, Chany Mony Dwiayu; Prisinda, Diani; Malinda, Yuti (Padjadjaran Journal of Dentistry, 2022)
Introduction: The primary aetiology of chronic periapical abscesses, including E. faecalis, S. mutans, S. sanguinis, and P. gingivalis, can be eliminated using intracanal medicaments such as calcium hydroxide. The purpose of this study was to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) value of calcium hydroxide paste in the vulnerable initial 7-day of treatment against E. faecalis ATCC 29212, S. mutans ATCC 25175, S. sanguinis ATCC 10556, and P. gingivalis ATCC 33277. Methods: An in-vitro laboratory experiment using a spectrophotometer as a microdilution method was conducted to determine bacteria's MIC and MBC values on calcium hydroxide paste. The sample used in this study was four bacteria using intracanal medicament of calcium hydroxide (Ca(OH)2), incubated for seven days at 37°C, and then bacterial growth was observed. The cell inhibition percentage was calculated using optical density measurements to determine the MIC value. The low MIC and MBC were defined as sensitive bacteria to calcium hydroxide. Results: Calcium hydroxide paste against E. faecalis (ATCC 29212) with MIC values at a concentration of 750 μg/ml and MBC values at a concentration of 96,000 μg ml; S. mutans (ATCC 25175) with MIC value at a concentration of 3,000 ug/ml and MBC value at a concentration of 48,000 ug/ml; S. sanguinis (ATCC 10556) with MIC value at a concentration of 3,000 ug/ml and MBC value at a concentration of 6,000 ug/ml; P. gingivalis (ATCC 33277) with MIC value at a concentration of 6,000 ug/ml and MBC value at a concentration of 48,000 ug ml. Conclusions: Calcium hydroxide can inhibit bacterial growth activity. E. faecalis (ATCC 29212) and S. sanguinis (ATCC 10556) are more sensitive to calcium hydroxide paste than other bacteria, with the lowest MIC and MBC on seven days of incubation since the maximum calcium and hydroxyl ions are released.